Red cell aspartate aminotransferase saturation with oral pyridoxine intake - Oshiro, Marilena; Nonoyama, Kimiyo; Oliveira, Raimundo Antonio Gomes; Barretto, Orlando Cesar de Oliveira (São Paulo Medical Journal, 2005)
CONTEXT AND OBJECTIVE: The coenzyme of aspartate aminotransferase is pyridoxal phosphate, generated from fresh vegetables containing pyridoxine. Vitamin B6-responsive sideroblastic anemia, myelofibrosis and Peyronie’s syndrome respond to high pyridoxine doses. The objective was to investigate the oral pyridoxine oral dose that would lead to maximized pyridoxal phosphate saturation of red cell aspartate aminotransferase. DESIGN AND SETTING: Controlled trial, in Hematology Division of Instituto Adolfo Lutz. METHODS: Red cell aspartate aminotransfe- rase activity was assayed (before and after) in normal volunteers who were given oral pyridoxine for 15-18 days (30 mg, 100 mg and 200 mg daily). In vitro study of blood from seven normal volunteers was also performed, with before and after assaying of aspartate aminotransferase activity. RESULTS: The in vivo study showed increasing aspartate aminotransferase saturation with increasing pyridoxine doses. 83% saturation was reached with 30 mg daily, 88% with 100 mg, and 93% with 200 mg after 20 days of oral supplementation. The in vitro study did not reach 100% saturation. CONCLUSIONS: Neither in vivo nor in vitro study demonstrated thorough aspartate aminotransferase saturation with its coenzyme pyridoxal phosphate in red cells, from increasing pyridoxine supplementation. However, the 200-mg dose could be employed safely in vitamin B6- responsive sideroblastic anemia, myeloﬁbrosis and Peyronie’s syndrome treatment. Although maximum saturation in circulating red cells is not achieved, erythroblasts and other nucleated and cytoplasmic organelles containing cells certainly will reach thorough saturation, which possibly explains the results obtained in these diseases.